The reasons for the low productivity of art education teachers in presenting school theater performances from their point of view (Journal of the College of Basic Education, 2023)
The research problem is determined by the following question: What are the reasons for the low productivity of art education teachers in presenting school theater performances from their point of view? What are the proposed solutions? As for the aim of the research, it is to identify the reasons for the low productive motivation of art education teachers to present theatrical performances from their point of view, so the research was limited to art education teachers who obtained a diploma working in the Diyala Education Directorate for the academic year (2022-2023) and whose service is less than (5) years. The researcher followed the descriptive approach to conduct the research, and he distributed a closed questionnaire to educational supervisors in the field of art education in order to ensure scientific, if there are actually scientific indicators that confirm what the researcher touched through his field of work, of a decrease in the motivation of teachers towards providing performances for school theater, either the research community consisted of art education teachers, it appeared that their number (124) teacher distributed to (62) befur (90) teachers only from holders of a diploma in the disciplines of art education.The researcher submitted an open questionnaire for the survey sample, and then identified a random sample, in which he asked to answer the basic question of the research, then the researcher emptied these answers in the form of paragraphs in the tool, then a research tool was built in the form of a questionnaire consisting of four main areas: (related to the school system - related to the student - related to the teacher Art education - related to the social environment), each area contains three paragraphs, so that the total paragraphs of the tool (12) paragraphs, extracted for it Psychometric properties and then presented to the statistical analysis sample to determine the weighted mean and relative weights for each field and paragraph